2013
DOI: 10.1177/1367493512468358
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ expectations and other factors affecting breastfeeding at six months in Greece

Abstract: The objective of this study is to determine the factors influencing breastfeeding duration in Greece. A total of 145 women were interviewed, on the third day post-partum. Women were followed up by telephone interviews at three and six months post-partum. Chi-square test and binomial sequential logistic regression analysis were used for statistical analysis. Results from this study show that baby-friendly hospital, antenatal courses, mother's perception of her capability to successfully breastfeed her infant, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…These are all factors strongly related to extended breastfeeding (18, 21, 22, 24) and thus highly important modifiable factors when promoting continued breastfeeding. Similar to our findings, several other studies conclude that antenatal breastfeeding education has a positive effect on breastfeeding knowledge (41-44) and education in the antenatal period seems to be more effective in increasing exclusive breastfeeding, partial breastfeeding (10) and breastfeeding knowledge levels (45). Consistent with the above findings, research has also shown that antenatal education has a positive impact on breastfeeding attitudes (41, 42) and on breastfeeding self-efficacy (46, 47).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These are all factors strongly related to extended breastfeeding (18, 21, 22, 24) and thus highly important modifiable factors when promoting continued breastfeeding. Similar to our findings, several other studies conclude that antenatal breastfeeding education has a positive effect on breastfeeding knowledge (41-44) and education in the antenatal period seems to be more effective in increasing exclusive breastfeeding, partial breastfeeding (10) and breastfeeding knowledge levels (45). Consistent with the above findings, research has also shown that antenatal education has a positive impact on breastfeeding attitudes (41, 42) and on breastfeeding self-efficacy (46, 47).…”
Section: Discussionsupporting
confidence: 91%
“…In Greece, the initiation rates of breastfeeding are high (85-94%) (9, 10), but breastfeeding rates decrease rapidly over the next months; to 55% after the first month (11) and to 12-22% at the end of the sixth month (10, 11). Exclusive breastfeeding rates at six months of age range from 0,3-23,4% (10, 11-13). However, these data lack of standardization of definitions and methods used to monitor breastfeeding rates and duration making it difficult to compare these rates among other countries.…”
Section: Introductionmentioning
confidence: 99%
“…We found that maternal educational attainment was a significant predictive factor for breast-feeding; this association is in fact one of the most consistent associations in the relevant literature (8,10,34,35) . We identified private insurance of the mother, an indicator of socio-economic status, to be independently associated with higher EBF at the 1st month.…”
Section: Discussionsupporting
confidence: 83%
“…Breastfeeding problem and caesarean delivery are well established risk factors for the cessation of exclusive breastfeeding [13, 28, 29]. Breastfeeding problems such as inverted, cracked or sore nipples can impact on the lactation decision and practice, while caesarean section can affect the secretion of breastmilk as well as the general health condition of the mother to exclusively breastfeed.…”
Section: Discussionmentioning
confidence: 99%